1969
DOI: 10.1136/gut.10.10.825
|View full text |Cite
|
Sign up to set email alerts
|

Insulin response to carbohydrate ingestion after gastric surgery with special reference to hypoglycaemia

Abstract: SUMMARY Factors responsible for spontaneous hypoglycaemia were investigated in 23 gastrectomy patients and two patients with vagotomy and pyloroplasty. Plasma insulin and capillary blood glucose levels were followed after giving 175 ml of 50% glucose orally. In gastrectomy patients a significant correlation was found between the height of the peak blood glucose and insulin levels for the same individual. Patients with high peak glucose and insulin levels were significantly more likely to develop hypoglycaemia … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1972
1972
2009
2009

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Griffith et al (1968) suggested that patients with uncomplicated duodenal ulcer have an abnormally rapid rate of gastric emptying soon after a meal. Rapid gastric emptying is known to result in a faster rate of rise of blood glucose concentration and higher peak levels in patients who have undergone partial gastrectomy or vagotomy and a drainage procedure (Evensen, 1942;Cameron et al, 1969;Holdsworth et al, 1969;Perreau et al, 1969). However, as the raised peak blood glucose levels are followed by an exaggerated fall towards hypoglycaemia this explanation alone will not account for the results which we have obtained in patients with duodenal ulcer.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Griffith et al (1968) suggested that patients with uncomplicated duodenal ulcer have an abnormally rapid rate of gastric emptying soon after a meal. Rapid gastric emptying is known to result in a faster rate of rise of blood glucose concentration and higher peak levels in patients who have undergone partial gastrectomy or vagotomy and a drainage procedure (Evensen, 1942;Cameron et al, 1969;Holdsworth et al, 1969;Perreau et al, 1969). However, as the raised peak blood glucose levels are followed by an exaggerated fall towards hypoglycaemia this explanation alone will not account for the results which we have obtained in patients with duodenal ulcer.…”
Section: Discussionmentioning
confidence: 99%
“…Abnormal glucose tolerance curves have been described after both partial gastrectomy and vagotomy and drainage, and have been attributed in large part to abnormaly rapid gastric empty- (Evensen, 1942;Cameron et al, 1969;Holdsworth et al, 1969;Perreau et al, 1969). Less attention has been paid to the question of carbohydrate metabolism in the preoperative ulcer patient.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, it has been repeatedly reported that shortly after glucose ingestion, subjects who have undergone gastric surgery with Billroth II type reconstruction, which in essence exclude duodenum and initial jejunum from food transit, could become hyperglycaemic and hyperinsulinaemic, compared with normal subjects [57]. Early hyperinsulinaemia has been related directly to early hyperglycaemia; the former being acknowledged as the cause of the reactive hypoglycaemia that was also frequently observed after this kind of operations reaching figures as high as 80% [58]. Interestingly, the same amount of glucose was found capable of producing a greater release of insulin when administered orally rather than intravenously in subjects with previous gastric surgery, suggesting that enteric factors participate in the control of insulin secretion after glucose ingestion [59].…”
Section: Surgical Proceduresmentioning
confidence: 99%